Mathematical literacy in the infant and adult phase of students in adult education programs - de Carvalho, Dione Lucchesi (Universidad Pedagógica y Tecnológica de Colombia, 2011)
This paper brings the deepening of an analysis of interviews done by participants of a post graduation course in Education with students of Adult Education Programs –EJA– in the region of Córdoba,Argentina. We underline the importance of the development of the theoreticalmethodological approaches about literacy, mainly those that consider it as cultural manifestation and are developed by deepening the studies of its autonomous and ideological dimensions. The analysis was developed through a theoretical-methodological interlocution with the bartonian critical ethnography. The interviewed students refer not only to numerical questions, but also to the measures and geometric aspects of mathematical literacy. In their speech, the aspects that point to the relations with the community are those that refer to the autonomy of options in the purchases, the desire to teach their artifact knowledge does not involve mathematical literacy.